Olympic Games as Mega-Sport Events: Some Social-Historical Reflections on Recent Summer Olympic Games - Dell’Aquila, Paolo (Italian Sociological Review, 2020)
This paper analyses the recent editions of Olympic Summer Games. It examines the changes and political, economical and cultural dimensions of mega-events, underlining the links among life, culture, mediascapes and cultural identities. The analysis starts with London Olympic Games 2012 and continues with the Games in Rio 2016: the primary changes in urban infrastructures and the social, political and economical transformation of the two cities together with the great impact of Olympic ceremonies in media images are introduced in the paper, with a particular reference to the symbolic representations of opening and closing ceremonies. The above mentioned events are an imaginative tour, which links knowledge, heritage, history and global values, demonstrating the interrelation between sport and other social spheres. Sport mega-events seem to create infinite world, connected with global and local culture. The opening and closing ceremonies represent also new symbolic values, and some ‘economies of imagination’, which reform urban infrastructures and open new social identity and heritage.